2018
DOI: 10.1002/slct.201800038
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Borylation of Alkynes and Alkenes

Abstract: The transition metal-free method for borylation of alkynes and alkenes with bis(pinacolato)diboron has been developed, producing the correspondent organoborons under mild reaction conditions. This reaction was an efficient, practical and environment-friendly process which brings forth vinylboronate products with excellent regioselectivity in the borylation of alkynes with bis(pinacolato)diboron, while in the meantime the diboryl alkanes were obtained using alkenes as substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…However, this hypothesis has not been proven yet. Another report appeared just a year later, which dealt with NaOMe as an initiator in the syn ‐hydroboration of terminal as well as internal alkynes (Scheme 17b) [81] . Notably, a trace of anti ‐hydroborated product was also obtained during this process.…”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
“…However, this hypothesis has not been proven yet. Another report appeared just a year later, which dealt with NaOMe as an initiator in the syn ‐hydroboration of terminal as well as internal alkynes (Scheme 17b) [81] . Notably, a trace of anti ‐hydroborated product was also obtained during this process.…”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
“…Several research groups have reported the regioselective and stereoselective hydroboration of alkynes and alkenes to produce vinyl boronates and alkyl boronate, catalyzed by transition metals such as Fe, Co, Cu, Ru, Rh, and Ir . Additionally, there are some reports of hydroboration of carbonyl compounds affording boronic esters, catalyzed by Co, Fe, and Ru. Main-group metal-catalyzed hydroboration of terminal alkynes and organic nitriles is also well reported in the literature. Using commercially available aluminum hydride ( i Bu 2 AlH) and LiAlH 4 or sodium borohydride (NaBH 4 ) is a well-known means of reduction of alkynes and alkenes, followed by aryl and alkyl nitriles . However, these reagents are combustible and generate large amounts of inorganic waste, which render the process unfavorable.…”
Section: Introductionmentioning
confidence: 99%
“…Product of single configuration can be obtained by advanced conditions especially rhodium catalytic system [66][67][68]. Hydroboration with diboride will generate 1,2-bis(boronates) [69] which can be further oxidated to vicinal diol (Scheme 6k). The participation of rhodium [70] and platinum [71] catalysts will lead to enantioselective products.…”
Section: Derivatization Strategies Of Phenylpropanoid Fragments 231 C...mentioning
confidence: 99%